(untitled) (International Journal of Food and Nutritional Sciences, 2022)
During the last decades some tragic episodes of contamination or illness have been attributed to the usage of some chemical products. This has driven some people to the assumption that “chemicals” are bad and harmful, while “natural” things are good and healthy. This fear towards “Chemicals” has been named chemophobia. This chemophobia forced people, researchers, scientists and different governments all over the world about clean, environmentally benign and non hazardous Chemistry. Green chemistry is a new philosophical approach for developing more effective chemical production and it is efficient, economical and environmentally friendly. It refers to reducing the damage done to the environment around us, it includes anything from reducing waste to even disposing of waste in the correct manner. To save our environment through green chemistry is to make use of renewable feedstock, biodegradable catalysts in experiments rather than using stoichiometric reagents. To manage our global environmental problems like curbing global warming, creating the clean energy future, protecting our health by preventing pollution, loss of biodiversity, natural resource depletion and environmental issues with agriculture we must need to drastically change the application of traditional scientific methodologies or technological culture.